Preparation method of recyclable carbon fiber reinforced ceramic-based composite material

By surface modification of carbon fiber and addition of nanoceramic particles, combined with intelligent monitoring and efficient separation technology, the shortcomings of carbon fiber reinforced ceramic matrix composite materials in recycling and resource recycling are solved, and efficient reuse and stable performance of materials are achieved. .

CN119390436APending Publication Date: 2025-02-07DEBAO CARBON CERAMICS (SUZHOU) TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411537739.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing carbon fiber reinforced ceramic matrix composite materials have shortcomings in recycling and resource recycling. The traditional recycling methods are costly and are prone to irreversible damage to the materials, and are difficult to meet the requirements of green manufacturing.

Method used

The carbon fiber is modified by surface treatment technology, combined with nanoceramic particles and functional dispersant, and the composite material is prepared by fiber laying method and gradient hot pressing process, and the reaction gas is introduced during the sintering process to improve the material performance. Material recycling and reuse using intelligent monitoring systems and efficient separation technologies such as supercritical fluid and electrochemical separation.

Benefits of technology

It realizes efficient separation and reuse of carbon fiber and ceramic matrix, ensures stable secondary use performance of the material, reduces recycling costs, and meets the requirements of green manufacturing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390436A_ABST
    Figure CN119390436A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of carbon fiber reinforced ceramic-based composite materials, in particular to a preparation method of a recyclable carbon fiber reinforced ceramic-based composite material, which comprises the following steps: carbon fiber pretreatment improvement, matrix material optimization, forming process innovation, sintering treatment optimization, intelligent monitoring system and recovery and fiber regeneration technology improvement. And the material recycling performance is improved. According to the method, the supercritical fluid and electrochemical separation technology is adopted, efficient separation of the carbon fibers and the matrix is achieved, meanwhile, the integrity and the recycling value of the fibers are ensured, and due to application of the self-repairing coating, surface damage of the recycled carbon fibers is repaired, the binding force of the carbon fibers and the matrix is enhanced, and the service life of the carbon fibers is prolonged. In addition, through introduction of an intelligent monitoring and feedback system, real-time monitoring and early warning in the material using process are achieved, and the safety and the service life of the material are guaranteed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of carbon fiber reinforced ceramic matrix composite materials, and in particular to a method for preparing a recyclable carbon fiber reinforced ceramic matrix composite material. Background Art

[0002] With the rapid development of science and technology, carbon fiber reinforced ceramic matrix composites have been widely used in high-end fields such as aerospace, automotive industry and energy due to their excellent mechanical properties, high temperature resistance and corrosion resistance. However, the existing preparation methods of carbon fiber reinforced ceramic matrix composites have obvious deficiencies in recycling and resource recovery. Once traditional composite materials reach the end of their service life or are damaged, they are often not able to be recycled efficiently. During the preparation process of most composite materials, a strong interface bond is formed between the carbon fiber and the ceramic matrix, making it difficult to separate and recycle the materials by conventional means after use. Traditional methods such as high temperature treatment or chemical separation are not only costly, but also easily cause irreversible damage to the material, causing the recycled carbon fiber to lose its original mechanical properties. In addition, these methods may cause pollution and are difficult to meet the requirements of green manufacturing. Summary of the invention

[0003] The purpose of the present invention is to solve the technical problems raised in the above background technology.

[0004] The present invention adopts the following technical solution: a method for preparing a recyclable carbon fiber reinforced ceramic matrix composite material, comprising the following steps:

[0005] S1: Surface treatment of carbon fiber, including surface oxidation treatment, coupling agent treatment, chemical coating treatment, or plasma treatment, wherein the plasma treatment improves the surface energy of carbon fiber and the interface bonding force between carbon fiber and ceramic matrix by controlling the treatment time and power, while reducing damage to the fiber surface;

[0006] S2: Silicate, silicon carbide, alumina or silicon nitride are selected as the ceramic matrix material, nano-ceramic particles (including nano-titanium dioxide or nano-silicon carbide) are added, and a functionalized dispersant is added, and the particles in the matrix material are ensured to be evenly dispersed by sufficient stirring to improve the mechanical properties, toughness and heat resistance of the composite material;

[0007] S3: Use fiber layering method, prepreg method, 3D printing technology or automatic fiber placement technology to mix carbon fiber and ceramic matrix material in proportion, combine computer numerical control equipment to accurately layout and control the fiber and matrix material, form preforms through mold hot pressing or injection molding, and use gradient hot pressing process to optimize temperature distribution and pressure during the molding process to improve the density of the preforms;

[0008] S4: The sintering is carried out in a high-temperature inert atmosphere or vacuum environment by gradually increasing the temperature. The thermal stress in the material is reduced by controlling the heating rate in different temperature ranges to prevent cracks in the composite material. Reactive gases (such as nitrogen or oxygen) are introduced to make the ceramic matrix material react during the sintering process to generate nitride or oxide ceramic phases, thereby improving the chemical stability and high-temperature performance of the material.

[0009] S5: During the sintering process and when the material is used, an intelligent monitoring and feedback system is added to monitor the material's temperature, stress and other working conditions in real time through sensors and data acquisition systems. When the material performance decreases, an early warning signal is issued to ensure the safety of the material and extend its service life;

[0010] S6: After the material is used, the carbon fiber is separated from the ceramic matrix by mechanical separation, supercritical fluid technology or electrochemical separation technology. Supercritical fluid is used to dissolve and remove the matrix residue. Electrochemical separation uses the electric field to strip the residual matrix on the fiber surface. The recycled carbon fiber is repaired by self-healing coating technology to enhance the interface bonding performance between the fiber and the ceramic matrix.

[0011] S7: Recycled carbon fiber and ceramic matrix are reused. The remanufactured composite materials are tested for performance (including tensile strength, fracture toughness, etc.) to ensure that they meet the physical and chemical performance requirements for reuse. The fiber recycling and matrix remanufacturing processes are continuously optimized through big data analysis and material databases to ensure the sustainability of material recycling and performance stability.

[0012] Preferably, the plasma treatment of the carbon fiber uses a gas medium of oxygen, nitrogen, argon or a mixed gas thereof, preferably a mixture of oxygen and argon, to further optimize the functional treatment of the carbon fiber surface. Here, the functional treatment of the carbon fiber surface is optimized, the interface bonding force between the carbon fiber and the ceramic matrix is ​​improved, the damage to the fiber surface is reduced, and the durability and mechanical properties of the material as a whole are enhanced.

[0013] Preferably, the surface oxidation treatment is carried out by wet oxidation or dry oxidation, wherein wet oxidation includes acid solution treatment, and dry oxidation uses high temperature oxidation or ultraviolet oxidation to enhance the chemical activity of the carbon fiber surface. Here, wet oxidation enhances the surface chemical activity, improves the wettability of the carbon fiber and the adhesion to the matrix material, and dry oxidation (such as high temperature oxidation, ultraviolet oxidation) ensures pollution-free treatment and improves the heat resistance of the composite material.

[0014] Preferably, the coupling agent treatment uses a silane coupling agent, and the coupling agent includes γ-aminopropyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane or a mixture thereof to further enhance the chemical bonding strength between the carbon fiber and the ceramic matrix. Here, the coupling agent treatment further enhances the chemical bonding between the carbon fiber and the ceramic matrix, reduces the risk of interface peeling, improves the long-term stability and chemical durability of the material, and is suitable for application in harsh environments.

[0015] Preferably, the preparation process of the matrix material uses ultrasonic dispersion technology, and the frequency range of ultrasonic waves is 20kHz to 40kHz, which is used to improve the uniform dispersion effect of nanoparticles in the ceramic matrix material. Here, ultrasonic dispersion ensures the uniform distribution of nanoparticles, reduces agglomeration, improves the uniformity of the composite material, and further improves the mechanical properties (such as strength and toughness) of the composite material, while enhancing heat resistance and oxidation resistance.

[0016] Preferably, the particle size of the nano ceramic particles ranges from 10 nm to 100 nm, preferably from 20 nm to 50 nm, to ensure a higher surface area and a reinforcing effect in the ceramic matrix material. Here, the smaller nano particle size provides a larger specific surface area, thereby significantly improving the reinforcing effect of the material, so as to show better strength, fracture toughness and high temperature performance.

[0017] Preferably, the fiber laying technology used in the molding process is a unidirectional laying method or a multidirectional laying method, and the anisotropic properties of the material are controlled according to different application requirements. The pressing pressure range of the gradient hot pressing process is 1MPa to 10MPa, and the temperature range is 500°C to 1800°C. Here, the unidirectional laying method and the multidirectional laying method enable the material to achieve anisotropic performance control according to different application requirements, and the gradient hot pressing process improves the material density, reduces internal defects, and improves mechanical properties by adjusting the temperature and pressure step by step.

[0018] Preferably, the working pressure of the supercritical fluid separation technology is 7.4MPa to 10MPa, the temperature range is 31°C to 50°C, the electrolyte used in the electrochemical separation technology is an acidic solution, an alkaline solution or an organic solution, and the stripping speed and efficiency of the ceramic matrix on the surface of the carbon fiber are controlled by adjusting the voltage and current density. Here, the supercritical fluid separation dissolves the residual matrix under low temperature and high pressure conditions to avoid damage to the carbon fiber, and the electrochemical separation achieves efficient stripping by precisely controlling the voltage and current, ensuring that the carbon fiber remains in good condition during the recycling process.

[0019] Preferably, after the recycled carbon fiber is treated with a self-repairing coating, the thickness of the surface coating is controlled to be between 1 μm and 10 μm, and the self-repairing coating includes an epoxy resin-based coating or a nanocomposite coating. Here, after the recycled carbon fiber is treated with a self-repairing coating, the surface damage is repaired, the mechanical properties and durability of the fiber are improved, and the self-repairing coating with a thickness of 1 μm to 10 μm enhances the bonding force between the carbon fiber and the matrix, ensuring that the secondary use performance of the composite material does not decrease.

[0020] Compared with the prior art, the advantages and positive effects of the present invention are:

[0021] In the present invention, supercritical fluid and electrochemical separation technology are used to achieve efficient separation of carbon fiber and matrix, while ensuring the integrity and reuse value of the fiber. The application of self-healing coating not only repairs the surface damage of the recycled carbon fiber, but also enhances its bonding with the matrix, so that the secondary use performance of the composite material remains stable. In addition, through the introduction of intelligent monitoring and feedback systems, real-time monitoring and early warning during the use of materials are achieved, ensuring the safety and service life of the materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The present invention provides a flow chart of a method for preparing a recyclable carbon fiber reinforced ceramic matrix composite material. DETAILED DESCRIPTION

[0023] In order to more clearly understand the above-mentioned purpose, features and advantages of the present invention, the present invention is further described below in conjunction with the accompanying drawings and embodiments. It should be noted that the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.

[0024] In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways than those described herein. Therefore, the present invention is not limited to the specific embodiments of the following disclosure.

[0025] Embodiment 1

[0026] See also Figure 1 The present invention provides a technical solution: a method for preparing a recyclable carbon fiber reinforced ceramic matrix composite material, comprising the following steps:

[0027] S1: Surface treatment of carbon fiber, including surface oxidation treatment, coupling agent treatment, chemical coating treatment, or plasma treatment, wherein the plasma treatment improves the surface energy of carbon fiber and the interface bonding force between carbon fiber and ceramic matrix by controlling the treatment time and power, while reducing damage to the fiber surface;

[0028] S2: Silicate, silicon carbide, alumina or silicon nitride are selected as the ceramic matrix material, nano-ceramic particles (including nano-titanium dioxide or nano-silicon carbide) are added, and a functionalized dispersant is added, and the particles in the matrix material are ensured to be evenly dispersed by sufficient stirring to improve the mechanical properties, toughness and heat resistance of the composite material;

[0029] S3: Use fiber layering method, prepreg method, 3D printing technology or automatic fiber placement technology to mix carbon fiber and ceramic matrix material in proportion, combine computer numerical control equipment to accurately layout and control the fiber and matrix material, form preforms through mold hot pressing or injection molding, and use gradient hot pressing process to optimize temperature distribution and pressure during the molding process to improve the density of the preforms;

[0030] S4: The sintering is carried out in a high-temperature inert atmosphere or vacuum environment by gradually increasing the temperature. The thermal stress in the material is reduced by controlling the heating rate in different temperature ranges to prevent cracks in the composite material. Reactive gases (such as nitrogen or oxygen) are introduced to make the ceramic matrix material react during the sintering process to generate nitride or oxide ceramic phases, thereby improving the chemical stability and high-temperature performance of the material.

[0031] S5: During the sintering process and when the material is used, an intelligent monitoring and feedback system is added to monitor the material's temperature, stress and other working conditions in real time through sensors and data acquisition systems. When the material performance decreases, an early warning signal is issued to ensure the safety of the material and extend its service life;

[0032] S6: After the material is used, the carbon fiber is separated from the ceramic matrix by mechanical separation, supercritical fluid technology or electrochemical separation technology. Supercritical fluid is used to dissolve and remove the matrix residue. Electrochemical separation uses the electric field to strip the residual matrix on the fiber surface. The recycled carbon fiber is repaired by self-healing coating technology to enhance the interface bonding performance between the fiber and the ceramic matrix.

[0033] S7: Recycled carbon fiber and ceramic matrix are reused. The remanufactured composite materials are tested for performance (including tensile strength, fracture toughness, etc.) to ensure that they meet the physical and chemical performance requirements for reuse. The fiber recycling and matrix remanufacturing processes are continuously optimized through big data analysis and material databases to ensure the sustainability of material recycling and performance stability.

[0034] In this embodiment, the plasma treatment of the carbon fiber uses a gas medium of oxygen, nitrogen, argon or a mixed gas thereof, preferably a mixture of oxygen and argon, to further optimize the functionalization treatment of the carbon fiber surface.

[0035] Specifically, the functional treatment of the carbon fiber surface was optimized, the interfacial bonding strength between the carbon fiber and the ceramic matrix was improved, the damage to the fiber surface was reduced, and the overall durability and mechanical properties of the material were enhanced.

[0036] In this embodiment, the surface oxidation treatment is performed by wet oxidation or dry oxidation. The wet oxidation includes acid solution treatment, and the dry oxidation uses high temperature oxidation or ultraviolet oxidation to enhance the chemical activity of the carbon fiber surface.

[0037] Specifically, wet oxidation enhances the surface chemical activity, improves the wettability of carbon fibers and the adhesion to the matrix material, while dry oxidation (such as high temperature oxidation and ultraviolet oxidation) ensures pollution-free treatment and improves the heat resistance of the composite material.

[0038] In this embodiment, the coupling agent treatment uses a silane coupling agent, and the coupling agent includes γ-aminopropyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane or a mixture thereof to further enhance the chemical bonding strength between the carbon fiber and the ceramic matrix.

[0039] Specifically, the coupling agent treatment further enhances the chemical bonding between the carbon fiber and the ceramic matrix, reduces the risk of interface debonding, and improves the long-term stability and chemical durability of the material, making it suitable for use in harsh environments.

[0040] In this embodiment, the preparation process of the matrix material uses ultrasonic dispersion technology, and the frequency range of ultrasonic waves is 20kHz to 40kHz, which is used to improve the uniform dispersion effect of nanoparticles in the ceramic matrix material.

[0041] Specifically, ultrasonic dispersion ensures uniform distribution of nanoparticles, reduces agglomeration, and improves the uniformity of the composite material. In addition, it improves the mechanical properties (such as strength and toughness) of the composite material while enhancing heat resistance and oxidation resistance.

[0042] In this embodiment, the particle size of the nano-ceramic particles ranges from 10 nm to 100 nm, preferably from 20 nm to 50 nm, to ensure a higher surface area and a reinforcing effect in the ceramic matrix material.

[0043] Specifically, smaller nanoparticle sizes provide a larger specific surface area, thereby significantly improving the reinforcement effect of the material so as to exhibit better strength, fracture toughness and high temperature performance.

[0044] In this embodiment, the fiber laying technology used in the molding process is a unidirectional laying method or a multidirectional laying method. The anisotropic properties of the material are controlled according to different application requirements. The pressing pressure range of the gradient hot pressing process is 1MPa to 10MPa, and the temperature range is 500℃ to 1800℃.

[0045] Specifically, the unidirectional lamination method and the multidirectional lamination method enable the material to achieve anisotropic performance control according to different application requirements. The gradient hot pressing process improves the material density, reduces internal defects and improves mechanical properties by gradually adjusting the temperature and pressure.

[0046] In this embodiment, the working pressure of the supercritical fluid separation technology is 7.4MPa to 10MPa, the temperature range is 31°C to 50°C, the electrolyte used in the electrochemical separation technology is an acidic solution, an alkaline solution or an organic solution, and the stripping speed and efficiency of the ceramic matrix on the carbon fiber surface are controlled by adjusting the voltage and current density.

[0047] Specifically, supercritical fluid separation dissolves the residual matrix under low temperature and high pressure conditions to avoid damage to the carbon fiber, and electrochemical separation achieves efficient stripping by precisely controlling voltage and current, ensuring that the carbon fiber remains in good condition during the recycling process.

[0048] In this embodiment, after the recycled carbon fiber is treated with a self-repairing coating, the thickness of the surface coating is controlled to be 1 μm to 10 μm, and the self-repairing coating includes an epoxy resin-based coating or a nano-composite coating.

[0049] Specifically, after the recycled carbon fiber is treated with the self-healing coating, the surface damage is repaired, which improves the mechanical properties and durability of the fiber. The self-healing coating with a thickness of 1μm to 10μm enhances the bonding force between the carbon fiber and the matrix, ensuring that the secondary use performance of the composite material does not decrease.

[0050] Embodiment 2

[0051] This embodiment is a preparation of a composite material of carbon fiber and silicon carbide ceramic matrix, which specifically includes the following steps:

[0052] a. Silicon carbide (SiC) was selected as the ceramic matrix material, and 20 nm nano-silicon carbide particles were added. The carbon fiber surface was treated with a plasma of a mixed gas of oxygen and argon for 30 minutes at a power of 150 W to enhance the interface bonding strength;

[0053] b. Add functionalized dispersants to the matrix material, use ultrasonic dispersion technology (frequency 30kHz) to ensure uniform dispersion of nanoparticles, use unidirectional lamination method to mix carbon fiber and ceramic matrix in a volume ratio of 70:30, and accurately lay them out using computer numerical control equipment;

[0054] c. Place the mixed material in a mold and use a gradient hot pressing process to form it at a pressure of 5MPa and a temperature of 1200°C to optimize density;

[0055] d. Gradually heat up to 1700°C in a vacuum environment at a rate of 5°C per minute to reduce internal stress and avoid crack formation. Nitrogen is introduced during the sintering process to generate partial silicon nitride phase and improve the high temperature resistance of the material;

[0056] e. Add intelligent monitoring system to detect temperature and pressure in real time to ensure the molding quality of materials;

[0057] f. After the material is used, supercritical carbon dioxide fluid separation technology (temperature 35°C, pressure 8MPa) is used to dissolve the matrix residues and a 5μm thick epoxy resin-based self-healing coating is coated on the surface of the recycled carbon fiber to enhance the interface bonding strength and ensure the stable performance of the material during secondary use.

[0058] Embodiment 3

[0059] This embodiment is a preparation of a composite material of carbon fiber and aluminum oxide matrix, which specifically includes the following steps:

[0060] a. Alumina (Al2O3) is selected as the matrix material, 30nm nano-titanium dioxide particles are added to enhance toughness, and the carbon fiber surface is wet oxidized (acid solution treatment) to further enhance the chemical activity of the fiber surface;

[0061] b. Use the multi-directional ply method to mix carbon fiber and matrix material in a ratio of 60:40, and control the directional layout of the fiber through a computer to achieve anisotropy control;

[0062] c. Use a pressing pressure of 10MPa and a temperature of 1500℃ for gradient hot pressing to ensure the density and uniformity of the material. Raise the temperature to 1800℃ at a rate of 3℃ per minute in a high-temperature inert gas, introduce oxygen to promote the formation of oxide phase in the matrix, and improve corrosion resistance;

[0063] d. Use embedded sensors to monitor the stress state of the material in real time and send out warning signals when the stress exceeds the threshold to prevent material failure;

[0064] e. Using electrochemical separation technology, select acidic electrolyte to remove matrix residues, and control the separation speed by adjusting the voltage;

[0065] f. The recycled carbon fiber is surface treated and coated with a 10μm thick nano-composite self-healing coating to ensure its durability in high temperature and corrosive environments.

[0066] The above description is only a preferred embodiment of the present invention and does not limit the present invention in other forms. Any technician familiar with the profession may use the technical content disclosed above to change or modify it into an equivalent embodiment with equivalent changes and apply it to other fields. However, any simple modification, equivalent change and modification made to the above embodiment based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing a recyclable carbon fiber reinforced ceramic matrix composite material, characterized in that: The following steps are involved: S1: Surface treatment of carbon fiber, including surface oxidation treatment, coupling agent treatment, chemical coating treatment, or plasma treatment, wherein the plasma treatment improves the surface energy of carbon fiber and the interface bonding force between carbon fiber and ceramic matrix by controlling the treatment time and power, while reducing damage to the fiber surface; S2: Silicate, silicon carbide, alumina or silicon nitride are selected as the ceramic matrix material, nano-ceramic particles (including nano-titanium dioxide or nano-silicon carbide) are added, and a functionalized dispersant is added, and the particles in the matrix material are ensured to be evenly dispersed by sufficient stirring to improve the mechanical properties, toughness and heat resistance of the composite material; S3: Use fiber layering method, prepreg method, 3D printing technology or automatic fiber placement technology to mix carbon fiber and ceramic matrix material in proportion, combine computer numerical control equipment to accurately layout and control the fiber and matrix material, form preforms through mold hot pressing or injection molding, and use gradient hot pressing process to optimize temperature distribution and pressure during the molding process to improve the density of the preforms; S4: The sintering is carried out in a high-temperature inert atmosphere or vacuum environment by gradually increasing the temperature. The thermal stress in the material is reduced by controlling the heating rate in different temperature ranges to prevent cracks in the composite material. Reactive gases (such as nitrogen or oxygen) are introduced to make the ceramic matrix material react during the sintering process to generate nitride or oxide ceramic phases, thereby improving the chemical stability and high-temperature performance of the material. S5: During the sintering process and when the material is used, an intelligent monitoring and feedback system is added to monitor the material's temperature, stress and other working conditions in real time through sensors and data acquisition systems. When the material performance decreases, an early warning signal is issued to ensure the safety of the material and extend its service life; S6: After the material is used, the carbon fiber is separated from the ceramic matrix by mechanical separation, supercritical fluid technology or electrochemical separation technology. Supercritical fluid is used to dissolve and remove the matrix residue. Electrochemical separation uses the electric field to strip the residual matrix on the fiber surface. The recycled carbon fiber is repaired by self-healing coating technology to enhance the interface bonding performance between the fiber and the ceramic matrix. S7: Recycled carbon fiber and ceramic matrix are reused. The remanufactured composite materials are tested for performance (including tensile strength, fracture toughness, etc.) to ensure that they meet the physical and chemical performance requirements for reuse. The fiber recycling and matrix remanufacturing processes are continuously optimized through big data analysis and material databases to ensure the sustainability of material recycling and performance stability.

2. The method for preparing a recyclable carbon fiber reinforced ceramic matrix composite material according to claim 1, characterized in that: The gas medium used in the plasma treatment of the carbon fiber is oxygen, nitrogen, argon or a mixed gas thereof, preferably a mixture of oxygen and argon, to further optimize the functionalization treatment of the carbon fiber surface.

3. The method for preparing a recyclable carbon fiber reinforced ceramic matrix composite material according to claim 1, characterized in that: The surface oxidation treatment is performed by wet oxidation or dry oxidation. The wet oxidation includes acid solution treatment, and the dry oxidation uses high temperature oxidation or ultraviolet oxidation to enhance the chemical activity of the carbon fiber surface.

4. The method for preparing a recyclable carbon fiber reinforced ceramic matrix composite material according to claim 1, characterized in that: The coupling agent treatment uses a silane coupling agent, which includes γ-aminopropyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane or a mixture thereof, to further enhance the chemical bonding strength between the carbon fiber and the ceramic matrix.

5. The method for preparing a recyclable carbon fiber reinforced ceramic matrix composite material according to claim 1, characterized in that: The preparation process of the matrix material uses ultrasonic dispersion technology, and the frequency range of ultrasonic waves is 20kHz to 40kHz, which is used to improve the uniform dispersion effect of nanoparticles in the ceramic matrix material.

6. The method for preparing a recyclable carbon fiber reinforced ceramic matrix composite material according to claim 1, characterized in that: The particle size of the nano-ceramic particles ranges from 10 nm to 100 nm, preferably from 20 nm to 50 nm, ensuring a higher surface area and a reinforcing effect in the ceramic matrix material.

7. The method for preparing a recyclable carbon fiber reinforced ceramic matrix composite material according to claim 1, characterized in that: The fiber laying technology used in the molding process is a unidirectional laying method or a multidirectional laying method, and the anisotropic properties of the material are controlled according to different application requirements. The pressing pressure range of the gradient hot pressing process is 1MPa to 10MPa, and the temperature range is 500°C to 1800°C.

8. The method for preparing a recyclable carbon fiber reinforced ceramic matrix composite material according to claim 1, characterized in that: The working pressure of the supercritical fluid separation technology is 7.4MPa to 10MPa, and the temperature range is 31°C to 50°C. The electrolyte used in the electrochemical separation technology is an acidic solution, an alkaline solution or an organic solution, and the stripping speed and efficiency of the ceramic matrix on the carbon fiber surface are controlled by adjusting the voltage and current density.

9. The method for preparing a recyclable carbon fiber reinforced ceramic matrix composite material according to claim 1, characterized in that: After the recycled carbon fiber is treated with a self-repairing coating, the thickness of the surface coating is controlled to be between 1 μm and 10 μm. The self-repairing coating includes an epoxy resin-based coating or a nano-composite coating.

Citation Information

Patent Citations

  • Recovery method of carbon fibers

    CN104499039A

  • Method for recovering carbon fibers by using supercritical fluid

    CN112048098A

  • Preparation method of carbon fiber reinforced ceramic-based composite material

    CN118005414A

  • Processing of carbon / carbon composites using supercritical fluid technology

    US5035921A